2022
DOI: 10.3389/fnmol.2022.810641
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Pivotal Role of CREB-Regulated Transcription Coactivator 1 in Depression and Comorbid Obesity

Abstract: Depression and obesity are major public health concerns, and there is mounting evidence that they share etiopathophysiological mechanisms. The neurobiological pathways involved in both mood and energy balance regulation are complex, multifactorial and still incompletely understood. As a coactivator of the pleiotropic transcription factor cAMP response element-binding protein (CREB), CREB-regulated transcription coactivator 1 (CRTC1) has recently emerged as a novel regulator of neuronal plasticity and brain fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 196 publications
(304 reference statements)
0
4
0
Order By: Relevance
“…Consistent with our results, Guo et al (2020) also confirmed that Erk1/2 inhibitor blocked the structural synaptic plasticity of testosterone on primary rat hippocampal neurons. Phospho-CREB may bind to the promoters of susceptibility genes associated with synaptic plasticity to enhance their transcription and then regulate brain functions ( Rossetti et al 2022 ). However, whether Erk1/2–CREB mediates the effect of testosterone on cognitive function and neuroprotection in vivo needs to be further demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Guo et al (2020) also confirmed that Erk1/2 inhibitor blocked the structural synaptic plasticity of testosterone on primary rat hippocampal neurons. Phospho-CREB may bind to the promoters of susceptibility genes associated with synaptic plasticity to enhance their transcription and then regulate brain functions ( Rossetti et al 2022 ). However, whether Erk1/2–CREB mediates the effect of testosterone on cognitive function and neuroprotection in vivo needs to be further demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Crtc1 is predominantly expressed in the brain [ 30 , 50 ] deleting this gene in mice induces a systemic metabolic deregulation [ 22 ], such as insulin resistance and obesity, together with a depressive-like phenotype [ 30 , 31 ]. As male Crtc1 −/− mice show a stronger depressive-like phenotype with a more severe comorbid obesity than females [ 21 , 23 , 29 ], we decided to capitalize on the former to focus on mechanistic aspects rather than sex differences in our neuroimaging study. While the association of MeS and behavioral alterations is likely to be complex and multifactorial, we report a clear link between brain glucose uptake and depressive-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CRTC1 has been implicated in rodent depressive-like behavior [23][24][25][26], which can be triggered by excessive CRTC1 phosphorylation and cytoplasmic sequestration as a response to chronic stress [27]. Thus, the Crtc1 knock-out (Crtc1 −/− ) mouse was shown to be a useful model to study the pathways and mechanisms linking metabolic diseases with depression [21,22,28,29] and to understand associated resistance to classic antidepressants, in particular to fluoxetine [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[54] In addition, proteins phosphorylated by protein kinase A and/or C may enter the nucleus and regulate gene transcription. One relevant example is the cAMP response element-binding protein (CREB), a transcription factor of interest in diseases of the central nervous system, [55][56][57][58][59] that can translocate from the cytoplasm to the nucleus.…”
Section: Signal Transduction In Bacteria and Mitochondriamentioning
confidence: 99%